Multiple infliximab biosimilar switches appear to be safe and effective in a real‐world inflammatory bowel disease cohort. Issue 2 (17th February 2023) - Gros, Beatriz; Plevris, Nikolas; Constantine‐Cooke, Nathan; Lyons, Mathew; O'Hare, Claire; Noble, Colin; Arnott, Ian D.; Jones, Gareth‐Rhys; Lees, Charlie W.; Derikx, Lauranne A. A. P.
Abstract: Background: Switching from originator infliximab (IFX) to biosimilar IFX is effective and safe. However, data on multiple switching are scarce. The Edinburgh inflammatory bowel disease (IBD) unit has undertaken three switch programmes: (1) Remicade to CT‐P13 (2016), (2) CT‐P13 to SB2 (2020), and (3) SB2 to CT‐P13 (2021). Objective: The primary endpoint of this study was to assess CT‐P13 persistence following switch from SB2. Secondary endpoints included persistence stratified by the number of biosimilar switches (single, double and triple), effectiveness and safety. Methods: We performed a prospective, observational, cohort study. All adult IBD patients on IFX biosimilar SB2 underwent an elective switch to CT‐P13. Patients were reviewed in a virtual biologic clinic with protocol driven collection of clinical disease activity, C‐reactive protein (CRP), faecal calprotectin (FC), IFX trough/antibody levels, and drug survival. Results: 297 patients (CD n  = 196 [66%], ulcerative colitis/inflammatory bowel disease unclassified n  = 101, [34%]) were switched (followed‐up: 7.5 months [6.8–8.1]). This was the third, second and first IFX switch for 67/297 (22.5%), 138/297 (46.5%) and 92/297 (31%) of the cohort respectively. 90.6% of patients remained on IFX during follow‐up. The number of switches was not independently associated with IFX persistence after adjusting for confounders. Clinical ( p  = 0.77), biochemical (CRP ≤5 mg/ml; p  = 0.75) and faecal biomarker (FC<250 µg/g; p  = 0.63) remission were comparable at baseline, week 12 and week 24. Conclusion: Multiple successive switches from IFX originator to biosimilars are effective and safe in patients with IBD, irrespective of the number of IFX switches. Abstract : Clinical, biochemical and faecal biomarker remission were comparable at baseline, week 12 and week 24. Number of switches was not independently associated with persistence after adjusting for confounders.